The predictive value of the preoperative diagnostic tests in mature cystic teratomas of the ovary - Saglam, Hanife; Atalay, Funda; Avsar, Ayse Filiz; Levent, Hüseyin (Clinical Journal of Obstetrics and Gynecology, 2018)
Aim: The aim of this study was to determine the sensitivity of the tumor markers and diagnostic methods used in the preoperative period for dermoid cysts, the most common benign neoplasm of the ovary. Material and Methods: 136 patients who were operated for any reason and reported as ovarian dermoid cyst in the Department of Obstetrics and Gynecology, Ankara Atatürk Training and Research Hospital between January 2004 and September 2005 were included in the study. The medical records of the cases were obtained retrospectively from Ankara-Atatürk Training and Research Hospital, HIS, archive files and patient numbers where necessary. Results: In the preoperative period, 119 patients underwent ultrasonographic examination, 33 underwent Computed Tomography, and 17 underwent Magnetic Resonance Imaging.10 of the cases only underwent CT, while 3 of the cases underwent only MRI 22 of them underwent both USG and CT, USG and MRI were performed on 13 cases and only 1 case underwent all three of the imaging methods. Tumor markers were CEA, CA 125, CA 19-9, CA 15-3 and AFP. Conclusions: The reviews of ultrasonography and / or computed tomography and / or magnetic resonance imaging (n = 132) revealed that 103 of the cases were put into operation and the sensitivity of the preoperative screening methods were calculated to be 75.5%. The sensitivity of the tumor marker CA 19-9 was calculated to be 31%.